113 Where Did the Ureteric Stent Disappear? – Mystery Solved. (28th February 2022) - Narayan, P.; Mukhtar, S.
Abstract: 38-year-old male presented to A&E with bilateral flank and suprapubic pain associated with mild VH. A CTKUB was suggestive of 10 cm ureteric stent noted in the left distal ureter and a few left sided lower calyceal non-obstructive stones. Patient denied any previous urological procedures or significant history. He even called up his mother in Hungary to ensure that. He was discharged with an outpatient follow up after his symptoms settled. In the clinic it was decided to carry out a CT Urogram and a flexible cystoscopy. The urine was also sent for cytology and acid-fast bacilli. His Calcium and urate profile was normal. On a CT Urogram, mysteriously the 10cm distal stent like calcification and the lower calyceal stones were not found, and on flexible cystoscopy the bladder looked pristine. The patient's symptoms had resolved, and he had not spotted passage of any stone as he was asked to stay vigilant. Discussion: Flexible cystoscopy along with CT Urogram was likely the best approach in this case- as it provided a holistic approach and excluded any upper tract pathology as well as a FB or abnormality in the urinary bladder.